Organochlorine Pesticide Dieldrin Suppresses Cellular Interferon-Related Antiviral Gene Expression. (29th May 2021) - Russo, Max; Humes, Sara T; Figueroa, Ariana M; Tagmount, Abderrahmane; Zhang, Ping; Loguinov, Alex; Lednicky, John A; Sabo-Attwood, Tara; Vulpe, Chris D; Liu, Bin
Abstract: Organochlorine pesticides (OCPs) are persistent pollutants linked to diverse adverse health outcomes. Environmental exposure to OCPs has been suggested to negatively impact the immune system but their effects on cellular antiviral responses remain unknown. Transcriptomic analysis of N27 rat dopaminergic neuronal cells unexpectedly detected high level expression of genes in the interferon (IFN)-related antiviral response pathways including the IFN-induced protein with tetratricopeptide repeats 1 and 2 ( Ifit1/2 ) and the MX Dynamin Like GTPases Mx1 and Mx2 . Interestingly, treatment of N27 cells with dieldrin markedly downregulated the expression of many of these genes. Dieldrin exterted a similar effect in inhibiting IFIT2 and MX1 gene expression in human SH-SY5Y neuronal cells induced by an RNA viral mimic, polyinosinic: polycytidylic acid (poly I:C) and IFIT2/3 gene expression in human pulmonary epithelial cells exposed to human influenza H1N1 virus. Mechanistically, dieldrin induced a rapid rise in levels of intracellular reactive oxygen species (iROS) and a decrease in intracellular glutathione (GSH) levels in SH-SY5Y cells. Treatment with N-acetylcysteine, an antioxidant and GSH biosynthesis precursor, effectively blocked both dieldrin-induced increases in iROS and its inhibition of poly I:C-induced upregulation of IFIT and MX gene expression, suggesting a role for intracellular oxidative status in dieldrin's modulation of antiviral gene expression. This study demonstrates that dieldrin modulates key genes of the cellular innate immune responses that are normally involved in the host's cellular defense against viral infections. Our findings have potential relevance to understanding the organismal effects of environmentally persistent organochlorine contaminants on the mammalian cellular immune system.